2014
DOI: 10.1002/gcc.22142
|View full text |Cite
|
Sign up to set email alerts
|

Cell cultures in uterine leiomyomas: Rapid disappearance of cells carrying MED12 mutations

Abstract: Uterine leiomyomas (UL) are the most frequent symptomatic human tumors. Nevertheless, their molecular pathogenesis is not yet fully understood. To learn more about the biology of these common neoplasms and their response to treatment, cell cultures derived from UL are a frequently used model system, but until recently appropriate genetic markers confirming their origin from the tumor cell population were lacking for most UL, i.e., those not displaying karyotypic abnormalities. The identification of MED12 mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 25 publications
3
40
1
Order By: Relevance
“…While UL-derived cell cultures are a wide-spread model system for research into the pathogenesis and behavior of the tumors [2, 911] recent results challenge the usefulness of this model for the group of tumors carrying MED12 mutations. Contrary to the expectations a rapid loss of mutated cells accompanied in vitro growth of UL-derived cell cultures [12]. As a rule, the mutations were not even detectable after early passages of in vitro growth resulting from so far unknown mechanisms.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…While UL-derived cell cultures are a wide-spread model system for research into the pathogenesis and behavior of the tumors [2, 911] recent results challenge the usefulness of this model for the group of tumors carrying MED12 mutations. Contrary to the expectations a rapid loss of mutated cells accompanied in vitro growth of UL-derived cell cultures [12]. As a rule, the mutations were not even detectable after early passages of in vitro growth resulting from so far unknown mechanisms.…”
Section: Introductionmentioning
confidence: 80%
“…This latter type of mutation occasionally can co-exist with chromosomal alterations except for those targeting HMGA2 [37] and clearly represents the most common type of driver mutations in UL. In vitro cells with this type of driver mutation recently were shown to coincide with a strictly reduced growth capacity in vitro , leading to their rapid disappearance in cell culture [12, 20]. In contrast, other cells from the samples not carrying these mutations of presumed non-tumorigenic origin as well as from tumors carrying HMGA2 rearrangements can survive much longer [12, 20].…”
Section: Discussionmentioning
confidence: 99%
“…The high concentration of TAFs explains why MED12 mutant cells are quickly lost from the primary culture of LMs (25,26); fibroblasts attach the culture dish better and grow faster than SMCs in standard culture conditions, conditions originally developed to optimize fibroblast growth (27). Overgrowth of fibroblasts is a classic problem for the primary culturing of SMCs including MM, and many techniques to repress the growth of fibroblasts in SMC culture have been proposed (20,28–32).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Bloch et al also suggested that the loss of MED12 mutant cells is partially due to the detachment of mutant cells from the culture flask, which likely reflects the weaker adherence of SMCs to the plastic surface compared to fibroblasts (40). Then, the subsequent passaging further dilutes SMCs in MED12-LM cell culture (25). Conversely, the low fibroblast concentration in HMGA2-LMs explains why HMGA2 mutant cells can be maintained in vitro for multiple passages (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation